(untitled) (Research, Society and Development, 2021)
Ozone therapy as an adjuvant in endodontic treatment has gained great space, due to its therapeutic properties such as antimicrobial action, tissue regeneration and healing potential, being one of the factors for the success of endodontics. Thus, Ozonoterapia presents several forms of application with potential for decontamination, through gas, water and ozonized oils, which can be used together or separately. Within this context, the objective of this work is to inform about the benefits and harms of the use of ozone as a therapeutic form in endodontics, in addition to clarifying how it emerged and its forms of action according to the form that it is used. The methodology used consisted of carrying out a narrative review of the literature, researched in scientific databases, such as: Scielo, Bvsalud, Redalyc and Sciencedirect. Thus, Ozonotherapy acts as an alternative therapy in endodontic treatment, being able to be used both in intracanal medications as an irrigating agent, able to act on bacteria, fungi, protozoa and viruses within the root canal system. It is concluded that ozone therapy as an aid in endodontic treatment is of great value, but that it is necessary to develop techniques that standardize the forms and time of ozone application.